2004
DOI: 10.1042/bj20030307
|View full text |Cite
|
Sign up to set email alerts
|

Human scavenger receptor class B type II (SR-BII) and cellular cholesterol efflux

Abstract: Although studies in recombinant cells indicate that scavenger receptor class B, type I (SR-BI) can promote cholesterol efflux, investigations in transgenic mice overexpressing or deficient in SR-BI endorse its physiological function as selectively sequestering cholesteryl esters from high-density lipoproteins (HDLs). Less clear is the role of SR-BII, a splice variant of the SR-B gene that differs only in the C-terminal cytoplasmic domain. Here, we identify several putative signalling motifs in the C-terminus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 39 publications
1
27
2
Order By: Relevance
“…These findings contrast with previous reports of the proportional distribution of these receptors in other tissues [30], and with our present survey across a wide range of cell types.…”
Section: Expression Of Hdl Receptors Sr-bi and Sr-biicontrasting
confidence: 57%
See 2 more Smart Citations
“…These findings contrast with previous reports of the proportional distribution of these receptors in other tissues [30], and with our present survey across a wide range of cell types.…”
Section: Expression Of Hdl Receptors Sr-bi and Sr-biicontrasting
confidence: 57%
“…It was the first authentic HDL binding protein to be characterized [51], although other ligands including apoE are now recognized [52]. A splice variant, termed SR-BII, was subsequently identified; this results from exon 12 skipping [30,53] to produce a receptor with a different C-terminal cytoplasmic tail, but identical extracellular binding region, to that of SR-BI. This implies differential functions; for example, the interaction between C-terminal SR-BI and PDZK1, a scaffolding protein [54], would not occur with SR-BII.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies have shown that the extracellular domain (ECD) of SR-B1 not only binds to ligands but also forms a hydrophobic channel for the trafficking of cholesterol esters (CE). It has been reported that caveolae present in cell membranes are the initial receiving sites of SR-B1-mediated CE intake, and 80% of CE accumulates in caveolae [24] . After discriminating HDL, SR-B1 forms a dimer via a leucine zipper region to construct a hydrophobic channel [25] .…”
Section: Four Trafficking Systemsmentioning
confidence: 99%
“…SR-BII, a spliced variant of the SR-B gene that differs from SR-BI only in the C-terminal cytoplasmic domain, also binds HDL with high affinity (27). In contrast to SR-BI, SR-BII does not mobilize intracellular cholesteryl ester stores and is less efficient at promoting cellular cholesterol efflux (27), but it effluxes 2-fold more FC than SR-BI in macrophages (28). Nonetheless, SR-BI and SR-BII both colocalize with cholesterolrich plasma membrane caveolae (28)(29)(30)(31), which influence cholesterol homeostasis by acting as conduits for cellular flux (32) and concentrate signaling proteins for signal transduction (33).…”
mentioning
confidence: 99%